Comparative anticonvulsant studies on ethanol and ethyl acetate extracts of Zingiber Officinale Roscoe rhizome in mice and chicks - Yakubu, Musa I; Enoch, Timothy; Abbas, Medinat Y; Abah, Johnson O; Jimoh, Abdulfatai A; Danbala, Ahmed A; Chindo, Ben A (Journal of Current Biomedical Research, 2022)
Epilepsy represents a major public health problem in low- and middle-income countries of Africa and Latin America where over 75% of patients do not have access to treatment. Aqueous and ethanol extracts of Zingiber officinale have been reported previously to have anticonvulsant effect. This study was aimed at comparing the anticonvulsant effect of ethanol and ethylacetate extracts of Zingiber officinale rhizomes in mice and chicks. Fresh rhizomes of Zingiber officinale (ginger) were collected, size reduced, air-dried under shade and extracted with ethanol and ethylacetate using cold maceration. Anticonvulsant activity of the extracts was determined by maximal electroshock stimulation (MES) in chicks, pentylenetetrazole (PTZ) and strychnine induced seizure models in mice. The ethanol and ethylacetate extracts of the ginger at doses of 50, 100 and 200 mg/kg were administered intraperitoneally 30 minutes prior to the induction of seizures. Both ethanol and ethylacetate extracts of Zingiber officinale at the doses of 100 and 200 mg/kg produced a dose-dependent protection against tonic hind limb extension seizure in MES model, significantly (p< 0.01) decreased the onset of clonic seizure in the strychnine model and significantly (p<0.001) prolonged the mean time of death in the PTZ model. In addition, the ethanol extract at the doses of 100 and 200 mg/kg significantly (p<0.001) decreased the onset of seizure in the PTZ model. It might be concluded that both ethanol and ethylacetate extracts of Zingiber officinale contain biologically active compounds with significant anticonvulsant activity, but the ethanol extract produced a better anticonvulsant activity.